Peningkatan Inovasi Superlizer Menggunakan Biokatalisator EM4 untuk Mempercepat Pertumbuhan Tanaman Cabai - Berlian, Muhammad Aminuddin; Pratama, Hamdan Ditya; Damayanti, Nur Aulia; Zulkarnaen, Maulana Dwi; Radianto, Denny Oktavina (VISA: Journal of Vision and Ideas, 2023)
Based on data obtained from BPS (Central Statistics Agency) in 2012 the number of farmers is 48% of the total workforce in Indonesia of around 49.8 million people (Alexandratos and Bruinsma 2012 p: 24). This situation is not enough to make Indonesia a prosperous and developed country. This is due to the low level of productivity of agricultural products because it is not supported by the use of good and environmentally friendly fertilizers. Farmers still often use chemical fertilizers which are capable of speeding up the planting period, but on the other hand in the long run it will actually have a risky negative impact. According to BPS dataon fisheries, shrimp production in Indonesia can reach 200,000 tons per year. The shrimp shell contains protein (25% - 40%), chitin (15% - 20%), and calcium carbonate (45% - 50%). The quality of shrimp shell waste based on nutrient content and nutrients is quite good and suitablefor use as liquid fertilizer, but until now this waste has not been used optimally, causing environmental pollution, especially odors and bad environmental aesthetics. The purpose of this study was to determine the process of making liquid organic fertilizer from shrimp shell waste (SUPERLIZER) and the effect of SUPERLIZER on the growth of chili plants. The method used in this study was to use 5 sample experiments with a comparison of the composition of shrimp shells and EM4 bacteria, namely (A) 200gram:100ml, (B) 300gram:100ml, (C) 400gram:100ml, (D) 500gram:100ml, (E) ) 600gram:100ml also used chemical fertilizer and water control which was tested for 10 days. The best results were obtained for sample (E) witha ratio of 600gram:100ml which gave a 5 cm increase in length compared to chemical fertilizers which only gave a 2.8 cm increase in length. Keywords: shrimp shells; liquid organic fertilizer; EM4 bacteria;